FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MP-ASI DINI DI PUSKESMAS GARUDA TAHUN 2016 - Widya Juliarti, Ranti Affriyani (Menara Ilmu, 2019)
Provision of complementary feeding (MP-ASI) early is the provision of food ordrink given to infants < 6 months. Based on preliminary studies in Puskesmas GarudaPekanbaru 2016 of 10 mothers with babies aged 0-6 months 7 states that the mother hadgiven complementary foods such as bananas, rice porridge, honey and milk formula. Thepurpose of this study to determine the factors that influence early complementary feeding.This research method is analytical observasional with cross sectional approach. This studywas conducted in March-April in Puskesmas Garuda Pekanbaru. The population in thisresearch is all mothers with babies aged 0-6 months. The sampling technique used wassimple random sampling with a sample of 67 mothers with babies 0-6 months. Analysis ofthe date used univariate and bivariate analysis with chi-square test.From the result of thisstudy indicate the factors that have a significant relationship to the provision of earlybreast milk is the knowledge (p=0,004), occupation (p=0,001) and confidence (p=0,003).While the factors that there is no significant relationship to the provision of early breastmilk are factors support health care workers (p=0,181). The final conclusion is thatknowledge, work, and trust has a significant connection to the provision of complementaryfeeding early, while health support has no significant relationship to the provision ofcomplementary feeding early. It is advisable to increase the role of health workers,particularly section maternal and child health through health promotion to mitivatemothers in exclusive breastfeeding and improve the mother’s knowledge about the righttime to give breast milk and explain the impact of complementary feeding prematureinfants < 6 months.Keywords: Early complementary feeding, Factors